2022
DOI: 10.1007/s11630-022-1694-6
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Plume Geothermal (CPG) Systems for Combined Heat and Power Production: an Evaluation of Various Plant Configurations

Abstract: CO2 Plume Geothermal (CPG) systems are a promising concept for utilising petrothermal resources in the context of a future carbon capture utilisation and sequestration economy. Petrothermal geothermal energy has a tremendous worldwide potential for decarbonising both the power and heating sectors. This paper investigates three potential CPG configurations for combined heating and power generation (CHP). The present work examines scenarios with reservoir depths of 4 km and 5 km, as well as required district hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Others assessed the reservoir heat depletion rates and well spacing designs, thermosiphon benefits in reducing pumping requirements, and increases in net electricity production. ,, Hansper et al analyzed the cost effectiveness of CPG systems and demonstrated that under preferred reservoir conditions and system layouts, they can be less expensive than brine-based systems in sedimentary basins. Schifflechner et al proposed combined heat and power (CHP) configurations for CPG systems, showcasing that such systems are suitable for deeper reservoirs (around 4 km) and can enhance the economic performance of CPG with revenues from heat compensating for reduction in power output.…”
Section: Introductionmentioning
confidence: 99%
“…Others assessed the reservoir heat depletion rates and well spacing designs, thermosiphon benefits in reducing pumping requirements, and increases in net electricity production. ,, Hansper et al analyzed the cost effectiveness of CPG systems and demonstrated that under preferred reservoir conditions and system layouts, they can be less expensive than brine-based systems in sedimentary basins. Schifflechner et al proposed combined heat and power (CHP) configurations for CPG systems, showcasing that such systems are suitable for deeper reservoirs (around 4 km) and can enhance the economic performance of CPG with revenues from heat compensating for reduction in power output.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, geothermal energy holds significant importance as a clean and stable energy source 8 . Additionally, geothermal energy can reduce reliance on fossil fuels, decrease dependence on imported energy, and enhance national energy security 9 . Therefore, the research on the extraction and utilization of geothermal resources in China becomes increasingly urgent 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Geothermal resources, as vast renewable and clean natural resources on Earth, are estimated to have an energy storage of approximately 3.6×10 14 gigawatt-hours in the upper 10 kilometers of the Earth's crust [1]. Theoretically, these geothermal reserves can supply global energy consumption for approximately 2.17 million years, based on a global energy consumption rate of approximately 1.7×10 8 gigawatt-hours per year in 2012 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…China, as the world's largest energy consumer and the second-largest economy, faces challenges of an insu ciently rational energy structure and limited environmental carrying capacity [12].In this context, geothermal energy holds signi cant importance as a clean and stable energy source [13]. Additionally, geothermal energy can reduce reliance on fossil fuels, decrease dependence on imported energy, and enhance national energy security [14]. Therefore, the research on the extraction and utilization of geothermal resources in China becomes increasingly urgent.…”
Section: Introductionmentioning
confidence: 99%